The Reproductive Toxicity of Mequindox in a Two-Generation Study in Wistar Rats - Liu, Qianying; Lei, Zhixin; Wu, Qin; Awais, Ihsan; Shabbir, Muhammad A. B.; Ahmed, Saeed; Fatima, Zainab; Wang, Xu; Pan, Yuanhu; Xie, Shuyu; Yuan, Zonghui (Frontiers in Pharmacology, 2018)
Mequindox (MEQ), belonging to quinoxaline-di-N-oxides (QdNOs), has been extensively used as a synthetic antibacterial agent. To evaluate the reproductive toxicity of MEQ, different concentrations of MEQ were administered to Wistar rats by feeding diets containing 0, 25, 55, 110 and 275 mg/kg, respectively. Each group consisting of 25 males and 25 females (F0) was treated with different concentrations of MEQ for 12-week period time, prior to mating and during mating, gestation, parturition and lactation. At weaning, 25 males and 25 females of F1 generation weanlings per group were randomly selected as parents for the F2 generation. Selected F1 weanlings were exposed to the same diet and treatment as their parents. The number of live litter and indexes of mating and fertility were significantly decreased in the F1 and F2 generation at 110 and 275 mg/kg groups. Significant decrease in pup vitality during lactation was observed in F1 litter at 275 mg/kg group, in F2 litter at 55, 110 and 275 mg/kg groups. A downward trend in the body weights was observed in F1 pups at 55, 110 and 275 mg/kg MEQ groups, and in F2 pups at 110 and 275 mg/kg MEQ groups. The changed levels of ALT, AST, CREA, BUN, UA, Na and K were noted in the serum of rats. The histopathologic examination showed that MEQ induced toxicity in the liver, kidney, adrenal, uterus and testis. The no-observed-adverse-effect level (NOAEL) for reproduction toxicity of MEQ was 25 mg/kg diet. The malformations and severe maternal toxicity of MEQ caused adverse effects on the conceptus and embryo, which result in fetal malformations and fetal deaths. In summary, the present study showed that MEQ induced maternal, embryo and reproductive toxicities as well as teratogenicity in rats.